Islam, Multikulturalisme, dan Pancasila - sahirul alim (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractIslam is not only a theological system; it has formed a holistic civilization, along with the history of humanity since more than 15 centuries ago. The doctrinal principles of Islam almost never conflict with cultural realities, except when these sacred teachings really hate anything which is contrary to human values. Islam recognizes the principle of multiculturalism as it is confirmed in the Qur’an. That is why, the process of islamization in Indonesia spread quickly and almost doctrinal matters of Islam were in accordance with the values of Indonesian tradition and culture. Indonesia is the largest Muslim country in the world, with a diversity of cultures, languages and religions (multiculturalism) but is able to maintain unity in the diversity of its society by adhering a state philosophy and ideology namely Pancasila. A unique experience of an “organic-multiculturalism” almost went unnoticed, that Pancasila was a synthesis of Islamic social values within multicultural circumstances integrating any diversities into the form of the “Negara Kesatuan Republik Indonesia” (NKRI).AbstrakIslam bukan hanya sistem teologis; Ia telah membentuk peradaban holistik, seiring dengan sejarah umat manusia sejak lebih dari 15 abad yang lalu. Prinsip doktrinal Islam hampir tidak pernah bertentangan dengan realitas budaya, kecuali jika ajaran sakral ini sangat membenci segala sesuatu yang bertentangan dengan nilai kemanusiaan. Islam mengakui prinsip multikulturalisme seperti yang ditegaskan dalam Al-Qur'an. Oleh karena itu, proses islamisasi di Indonesia menyebar dengan cepat dan hampir semua masalah doktrinal Islam sesuai dengan nilai-nilai tradisi dan budaya Indonesia. Indonesia merupakan negara muslim terbesar di dunia, dengan keragaman budaya, bahasa dan agama (multikulturalisme) namun mampu menjaga persatuan dalam keberagaman masyarakatnya dengan menganut falsafah dan ideologi negara yaitu Pancasila. Pengalaman unik dari “multikulturalisme organik” hampir luput dari perhatian, bahwa Pancasila merupakan sintesis nilai-nilai sosial Islam dalam lingkungan multikultural yang mengintegrasikan keragaman ke dalam bentuk “Negara Kesatuan Republik Indonesia” (NKRI).